Implementation of Lumi-Based ESD Learning to Train Systems Thinking and Digital Literacy in the Context of SDGs 15 - Insyira, Syifa Maulani; Suhendar, Suhendar; Adhi Prasetyo; Nuranti, Gina (BIOEDUSCIENCE, 2025)
Background: This research is motivated by students' systems thinking competence and digital literacy, which are still very low. This is due to the delivery of biodiversity material, which is still very conventional, and learning that is still teacher-centred. Therefore, this research will use the application of Lumi-based ESD learning. This research aims to determine the effect of implementing Lumi-based ESD learning to train systems thinking and digital literacy in the context of SDGs 15. Method: The type of research used in this research is Quasi Experiment with a Non-Equivalent Control Group Design research design. The sampling technique uses purposive sampling, namely class X1 as the experimental class and X5 as the control class. The instruments used were systems thinking competency tests, digital literacy questionnaires, attitude scale sheets, and student response questionnaires. Results: The research results stated that the N-Gain Value of systems thinking competency in the experimental class was outstanding, with a value of 0.65 in the medium category compared to the control class, with a value of 0.29 in the low category. Meanwhile, the N-Gain digital literacy value of students in the experimental class, with a value of 0.45 in the medium category, was compared with the control class, with a value of 0.18 in the low category. Judging from the hypothesis test, systems thinking, and digital literacy show significant differences with both values at sig (2-tailed) 0.00. Conclusion: From this research, it can be concluded that applying Lumibased ESD learning affects practicing systems thinking and digital literacy in SDGs 15. The findings in this research are that applying Lumi-based ESD learning is much better for practicing systems thinking competencies than digital literacy.